Therapeutics of pilocarpine - Cassell, Albert F. (My University, 1907)
Introduction: HABITAT. Pilocarpine is an alkaloid of Pilocarpus, and to this primary action the crude drug owes its principal effect. The plant from which pilocarpine is derived grows in Brazil, South America. DESCRIPTION. It is about ten (10) to fifteen (15) C.M. long and from four (4) to six (6) C.M. broad. Short stalk, of a dull green color, coriaceous, pellucid- punctuate, mostly smooth; when bruised, slightly aromatic. Taste somewhat bitter and pungent.CONSTITUENTS. From this plant several other alkaloidal products are derived such as Jaborine C22H32N4O4; Pilocarpudine C10H14N2O2;Jaborandine whose composition is not exactly known. Pilocarpine is the hydrochlorate of an alkaloid obtained from pilocarpus with alcohol and hydrochloric acid by distillation and evaporation. The residue is dissolved in a slight excess of ammonia and chloroform, shaken with water, and then neutralized with hydrochloric acid. On evaporation crystals of hydrochlorate are formed. The properties of filocarpine,small white crystals having no odor but slightly bitter taste, are very soluble in water and alcohol, but almost insoluble in ether or chloroform. The drug can be used for a sialogogue cathartic or diaphoretic. Depending on the dose and for the end to which it is intended.
Citation: Cassell, Albert F. Therapeutics of pilocarpine. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Pilocarpine; Pharmaceuticals; Drug Composition; Theses